Erectile Dysfunction Is Associated With Excessive Growth Hormone Levels in Male Patients With Acromegaly - Chen, Zhengyuan; Shao, Xiaoqing; He, Min; Shen, Ming; Gong, Wei; Wang, Meng; Zhang, Yichao; Liu, Wenjuan; Ma, Zengyi; Ye, Zhao; Lu, Yongning; Yang, Nianqin; et al. (Frontiers in Endocrinology, 2021)
Objective To determine the risk factors for erectile dysfunction (ED) in male patients with acromegaly and to prospectively investigate the short-term changes of erectile function after surgery or medical treatment. Methods Sixty-three male patients were subjected to nocturnal penile tumescence and rigidity (NPTR) test for the evaluation of erectile function. The measurement of serum nitric oxide (NO) was also performed. Twenty-seven patients were re-evaluated by NPTR after surgery or long-term somatostatin analogues (SSA) treatment. Results Twenty-two patients (34.9%) had ED. Patients with ED showed higher random GH (17.89 [10.97-44.19] μg/L vs 11.63 [4.31-28.80] μg/L, p = 0.020) and GH nadir (GHn) (10.80 [6.69-38.30] μg/L vs 8.76 [3.62-18.19] μg/L, p = 0.044) during oral glucose tolerance test (OGTT). The NO levels of ED patients were lower than non-ED patients (9.15 [5.58-22.48] μmol/L vs 16.50 [12.33-31.78] μmol/L, p = 0.012). After treatment, patients who present improvement in erectile function showed lower post-GHn (0.07 [0.03-0.12] ng/ml vs 1.32 [0.09-3.60] ng/ml, p = 0.048) and post-IGF-1 index (1.03 ± 0.38 vs 1.66 ± 0.95, p = 0.049). The multivariate analysis indicated post-GHn was still associated with the improvement of erectile function after correction of other covariates (OR: 0.059, 95% CI: 0.003-1.043, p = 0.053). Conclusions Excessive GH is related to ED in male patients with acromegaly. GH normalization after treatment is beneficial for short-term erectile function recovery.